Trends and Emerging Innovations in Digital Media for E-Module Development: A Systematic Literature Review - Maria Veronica Deno; Khaerudin; Dwi Kusumawardani (Universitas Pendidikan Mandalika, 2026)
This study aims to conduct a comprehensive mapping of the evolution of digital media in e-module development over the past five years (2020–2024). Furthermore, it seeks to identify research gaps to provide a strategic roadmap for the future development of e-modules integrated with Artificial Intelligence (AI) and immersive media. Adopting the PRISMA 2020 protocol, a Systematic Literature Review (SLR) was conducted on Scopus-indexed articles. From the selection process, 20 articles were analyzed through a systematic process of categorization and synthesis based on research types, pedagogical approaches, and the digital media and platforms used. The findings indicate the dominance of R&D methods, particularly the ADDIE and 4D models. Pedagogical approaches such as Problem-Based Learning, STEM, SETS, Discovery Learning, and Guided Inquiry consistently improve critical thinking skills, learning outcomes, and 21st-century competencies. In terms of technology, Android-based platforms and flipbooks are the most preferred due to their accessibility and support for multimedia elements such as videos, animations, simulations, and interactive quizzes. These findings highlight the importance of developing e-modules that are systematic, pedagogically grounded, constructivist, and supported by interactive multimedia. Future research needs to explore the integration of AR/VR, gamification, and artificial intelligence.